(untitled) (Research Journal, 2024)
This paper examines the emerging trends and major issues related to remittance inflows in Nepal, within the context of the broader global migration landscape. Nepal’s reliance on remittance is a proof to the increasingly globalized nature of labor migration. The inflow of remittance has become a crucial component of Nepal’s economy, contributing significantly to the nation’s economic growth and stability. The objective of this study is to identify the flow of remittance and its utilization in the study area. Study is prepared on primary sources and descriptive design. The study is based on the quantitative nature. Out of 261 foreign labor migrants’ people, about one third people (32.5%) were sent money for remittance less than five lakhs per year and less than one percent (0.8%) people were sent more than twenty-five lakhs per year from foreign country. Majority of the households (34.7%) have been spent their remittance in household expenditure and only few (0.7%) households for health care and treatment. Migration improved quality of life and economic stability for 88% of migrant households, with 40% able to buy land, 32% access quality education, and 17.7% improving relationships. Over 80% of households saw an additional burden on women as a result of foreign labor migration, with 29.7% having difficulty caring for children and the elderly. Over 75.2% reported troubled children, a lack of supervision, family collapse, and loneliness, with 9.6% facing the extra stress of loneliness. Only 0.3% reported feeling lazy or uninterested in their task. Government agencies and local government take effective action. Agriculture should be modernized and professionalized to reduce the rate of going foreign employment. Effective policy and strategy should be implemented for livelihood by the government of Nepal. As results we can reduce the problems and challenges which occur due to foreign employment